HUBUNGAN KEKUATAN OTOT PUNGGUNG DAN KEKUATAN OTOT TUNGKAI TERHADAP KECEPATAN CLOSE DRIBBLE PADA ATLET PUTRA HOCKEY INDOOR KOTA METRO - Suryono, Rizki; Dinata, Marta; Rifaldo, Muhammad Fajril; Priyono, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between back muscle strength and leg muscle strength to close dribble speed in indoor hockey games in male athletes in Metro City. The research method used is a survey method with a sample of 25 male hockey athletes in Metro City. The research instruments used include a back and lag dynamometer test to measure back muscle strength and leg muscle strength, and a close dribble speed test using the Field Hockey-Specific Dribbling Speed ​​Test. Research hypotheses: 1) there is a relationship between back muscle strength and close dribble speed, 2) there is a relationship between leg muscle strength and close dribble speed, 3) there is a relationship between back muscle strength and leg muscle strength and close dribble speed. The results of the study showed that: 1) there is a significant relationship between back muscle strength and close dribble speed (r count = 0.501 > r table = 0.413), 2) there is a significant relationship between leg muscle strength and close dribble speed (r count = 0.558 > r table = 0.413), 3) Simultaneously, back muscle strength and leg muscle strength also have a significant relationship to close dribble speed (r count = 0.527 > r table = 0.413) with a contribution of 27.84%.